노안교정을 위한 굴절형 각막 인레이의 장기간 임상 결과 - 최영주; 한겨레; 임동희; 정태영 (Daihan angwa haghoi jabji, 2023)
목적: 한국인에서 노안교정을 위한 Flexivue Microlens의 효능과 안전성에 대한 장기간 임상 결과를 분석하였다. 대상과 방법: 2015년 10월부터 2018년 2월까지 삼성서울병원에서 Flexivue Microlens를 삽입한 환자 9명을 대상으로 하였고, 평균추적 기간은 1.95 ± 0.6년이었다. 수술 전후 시력, 구면렌즈대응치, 대비감도, 탈초점곡선, 환자 만족도에 대해 후향적으로 의무기록을 분석하였다. 결과: 삽입안의 근거리 나안시력은 술 후 6개월에 0.27 ± 0.10 logarithm of the minimal angle resolution (logMAR)으로 향상되었고(p=0.012), 마지막 관찰 시 0.32 ± 0.21 logMAR로 술 전에 비해 개선되었으나 유의한 차이는 없었다(p=0.127). 양안 근거리 나안시력은 술 후 6개월과 마지막 관찰 시 각각 0.19 ± 0.78 logMAR, 0.21 ± 0.13 logMAR로 향상되었다(p=0.017, p=0.028). 삽입안의 원거리 나안시력은 술 후 6개월과 마지막 관찰 시 각각 0.38 ± 0.15 logMAR, 0.32 ± 0.21 logMAR로 감소하였으나(p=0.007, p=0.012), 양안에서는 수술 전후 차이가 없었다. 근거리 시력에 대한 만족도는 유의하게 향상되었으며, 4점(만족) 이상은 14.3%였고 근거리 안경을 착용하지 않는 비율은 42.9%였다. 1명은 흐려 보임으로 1년 5개월째 인레이를 제거하였다. 결론: Flexivue Microlens는 합병증 위험이 낮고 가역적이지만, 근거리 시력 개선이 단기적이고 원거리 시력이 저하되었다. 또한 한국인에서 만족도가 낮고 안경 의존도가 높았다. Purpose: To study the long-term efficacy and safety of Flexivue Microlens refractive corneal inlays in Koreans for compensation of presbyopia. Methods: Flexivue Microlens inlays were implanted in nine eyes at Samsung Medical Center from October 2015 to February 2018. The follow-up period was 1.95 ± 0.6 years. Pre- and postoperative near/intermediate/distant visual acuity, spherical equivalent, contrast sensitivity, defocus curve, keratometry, and patient satisfaction were evaluated retrospectively. Results: The uncorrected near visual acuity (UNVA) of the operated eye increased significantly to 0.27 ± 0.10 logarithm of the minimal angle resolution (logMAR) after 6 months (p = 0.012). At the last observation, it was 0.32 ± 0.21 logMAR, which improved compared to before surgery, but the difference was not significant (p = 0.127). The binocular UNVA improved significantly to 0.19 ± 0.78 logMAR at 6 months postoperatively (p = 0.017) and to 0.21 ± 0.13 logMAR at the last observation (p = 0.028). There was no difference in the binocular uncorrected distant visual acuity (UDVA) before and after surgery, but the UDVA of the operated eye decreased significantly to 0.38 ± 0.15 logMAR at 6 months postoperatively (p = 0.007) and to 0.32 ± 0.21 logMAR at the last observation (p = 0.012). Satisfaction with near vision improved significantly after surgery; 14.3% of the patients had a score of 4 (good) or higher and 42.9% did not require near-vision glasses. In one case, the inlay was removed after 17 months due to blurred vision. Conclusions: The Flexivue Microlens has a low risk of complications and is a reversible technique. However, the near vision improvement was temporary and distance vision deteriorated. In addition, the Koreans examined had relatively low satisfaction and high spectacle dependence. KCI Citation Count: 0